(untitled) (UNED Research Journal, 2020)
Introduction: In Costa Rica, paraquat is the third most imported pesticide and it is widely applied in different plantations. This makes it necessary to have a strict quality control for compliance with local regulations Objective: To verify and compare AOAC standard methods 969.09 by UV-Vis spectrometry and the respective CIPAC method by HPLC. Method: The guidelines described by the Costa Rican Accreditation Body (ECA) were followed to verify analytical performance parameters in standardized methods. Results: The UV and HPLC methods proved suitable but had significant differences in the results. Conclusions: Both methodologies comply with the requirements but we recommend an enlarged test with more analysts and laboratories to define which is more accurate.